Seaweed extracts: enhancing plant resilience to biotic and abiotic stresses - Gagan Kumar; Satyabrata Nanda; Satyabrata Nanda; Sushil Kumar Singh; Sanjeet Kumar; Divya Singh; Bansh Narayan Singh; Arpan Mukherjee (Frontiers in Marine Science)
Seaweeds are a natural marine resource containing many bioactive compounds such as amino acids, lipids, carbohydrates, proteins, phytohormones, and antimicrobial compounds. Since ancient times, seaweeds have been used in various sectors, including medicine, food, and the cosmetic industry. Currently, seaweeds are a promising alternative to reduce the application of harmful chemicals in agriculture. Seaweed and its derived products have been utilized for plant growth promotion, immunity enhancement, and the reduction of biotic and abiotic stresses. In the current global scenario, synthetic fertilizers and chemical pesticides are commonly used to increase agricultural crop production to meet the growing demands of the world population. However, these chemicals pose significant threats to the health of people, livestock, plants, soil, and the entire environment. In contrast, seaweed-based products are emerging as a newer option for stress mitigation and reduction, offering an alternative to synthetic chemicals. This article explains the use of seaweed extracts to increase the tolerance of plants to biotic and abiotic stresses. We also address the functions of various bioactive compounds present in seaweed extracts and the mechanisms by which they promote plant growth and induce defense against different stresses.